Appraisal of risky behaviour of youth populace: a vulnerable venture - Nagalingam, Saranya; Arumugam, Balaji; Khanna, Rohith; Krishnasamy, Sudharsson (International Journal Of Community Medicine And Public Health, 2017)
Background: Effectiveness of the public health is determined by assessing the wellbeing of the general populace. The vulnerability to high risk behaviours during adolescence contributes to high prevalence of morbidity and mortality among the future generation. The sobriety of these vulnerable behaviours may even lead to early pregnancy due to sexual promiscuity, addiction to drugs ultimately leading to teenage delinquency. Main objective of the study is to assess the risk behaviours in relation to accident proneness, smoking habits, alcohol use, and sexual promiscuity among college going youth populace in southern part of Chennai, India. Methods: A cross sectional study was conducted using an internationally standardized questionnaire - the youth risk behaviour scale among youth population by direct interview method. The colleges were randomly selected using simple random sampling method and the partakers were interviewed after getting assent from the concerned institutions. The sample size was calculated as 100 from WHO global health observatory data prevalence of tobacco usage as 51%. Results: The investigator had interviewed 127 study participants from various colleges of which majority 73% were males and 80% of them belonged to urban area. The behaviours like drunken drive, texting while driving, carrying a weapon, physical fight was seen among 12.5%, 40%, 4% and 4% respectively. Approximately 8.7% seriously thought of committing suicide of which 1.6% of them attempted suicide more than 2 times. The smoking and alcohol drinking habits were present among 22% and 26% respectively. Around 4.8% had multiple sex partners of which 5.5% of them do not use condoms and 1.6% had gay relationship. Conclusion: The results of this survey are alarming that the college going youth population fail to understand the devastating consequences of high - risk behaviours. Hence, interventions must be designed to prevent high risk behaviours among the vulnerable population.